Anti-PD-1 combined with hypomethylating agent and CAG regimen bridging to allogeneic hematopoietic stem cell transplantation: a novel strategy for relapsed/refractory acute myeloid leukemia - Wang, Yu-Xin; Wang, An; Su, Yong-Feng; Wang, Jun; Li, Yu-Hang; Li, Fei; Jing, Yu; Xu, Lei; Wang, Yi-Zhi; Zheng, Xuan; Gao, Chun-Ji; Hu, Liang-Ding; et al. (Frontiers in Immunology, 2024)
The prognosis of relapsed/refractory acute myeloid leukemia (r/rAML) is dismal, and allogeneic hematopoietic stem cell transplant (allo-HSCT) is a potential cure. Combining anti-PD-1, hypomethylating agent (HMA), and CAG (cytarabine, aclarubicin/ idarubicin, granulocyte colony-stimulating factor) regimen has showed primary efficacy in r/rAML. However, pre-transplant exposure to anti-PD-1 may lead to severe graft-versus-host disease (GVHD). This preliminary study aimed to evaluate the safety and efficacy of allo-HSCT in r/rAML patients receiving the anti-PD-1+HMA+CAG regimen. Fifteen r/rAML patients (12 related haploidentical donors [HIDs], 2 matched siblings, 1 unrelated donor) received this regimen and subsequent peripheral blood HSCT. Four patients with HIDs received a GVHD prophylaxis regimen consisted of Anti-thymocyte globulin and a reduced-dose of post-transplant cyclophosphamide. The median follow-up was 20.9 months (range, 1.2-34.2). The cumulative incidences of acute GVHD grade 2-4 and grade 3-4 were 40% and 13.3%, respectively. The 2-year incidence of moderate-to-severe chronic GVHD, non-relapse mortality , and relapse were 10%, 22.3%, and 22.5%, respectively. The 2-year overall survival and GVHD-free/relapse-free survival rates were 54% and 48.6%, respectively. No death or relapse was observed in the PTCy group. The anti-PD-1+HMA+CAG regimen bridging to allo-HSCT for r/r AML was tolerable with promising efficacy. GVHD prophylaxis with PTCy for HID-HSCT showed preliminary survival advantage.